Ways of world experience in flipped learning implementation for foreign language training - Udartseva, T.S.; DeVeroux, C.; Druzhinina, N.V. (KU publ., 2020)
Inthearticletheauthorsconsiderthe concept of flipped learning method, its features and constituent components. Flippedlearning (FL) is a pedagogical method aimed at traditional education system transformation. FL method implies the shift of activities performed in group and in individual space (activities previously done in class, now students do outside of class). Due to insufficient level FL application study in homeland education system, authors focused on studying of FL effectiveness in the process of English language teaching as a foreign language at universities of 5 countries: Russia, Egypt, Ecuador, Thailand and Indonesia. The universities selection for study was carried out according to such criteria as: level of education, English language study as a foreign language, FL elements implementation in students training, using feedback at the end of the course study.According to the carries out analysis, all participants of educational process demonstrated positive attitude to FL use at5 universities, among leading positive points were mentioned the following: improvement in language proficiency level, increase in the level of students’independent work in organizing their studies, possibility of digital technologies wide implementation in educational process.As the results of performedanalysis at foreign universities in the field of FL method implementation in language training, the authors carried out SWOT analysis, which makes it possible to determine presence of opportunities, difficulties and threats for FL implementation in the process of foreign language training at homelanduniversity.
Шет тілін дайындауда төңкерілген оқыту əдісін қолданудың əлемдік тəжірибесін бейімдеу жолдары
Пути адаптации мирового опыта использования метода перевернутого обучения в иноязычной подготовке
Keywords: foreign language; flipped learning; individual space; group space; SWOT-analysis; digital platform; active learning methods; traditional system of education